Как хорошо уметь читать...: стихи / Валентин Берестов ; [художники Н. В. Кузнецова, О. Ю. Горбшин] - Берестов Валентин Дмитриевич (Детские классики, 2007)
Экземпляры: ф12/13/14/15 (20250113) / Инвентарный номер: 43210 / Цена: 54.60 / Сис.шифр: Р2мл / Авт.знак: Б 48 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6